The 16 April 2016 Ecuador Earthquake Damage Assessment Survey. Issue 3 (August 2018) - Villalobos, Enrique; Sim, Chungwook; Smith-Pardo, J. Paul; Rojas, Pedro; Pujol, Santiago; Kreger, Michael E.
A damage assessment survey of 169 low-rise reinforced concrete buildings was conducted following the 16 April 2016 Ecuador earthquake. Forty-four percent of the buildings surveyed sustained severe structural damage. Using the collected data, seismic vulnerability indices were calculated to examine their correlation with damage observations. It was found that 92% of the buildings with observed severe structural damage had calculated wall and column index pairs (WI, CI) that satisfied the relation WI+CI/2 < 0.2%. The frequency of damage was lower for higher-priority index values, defined as the sum of CI+WI. Furthermore, frequency of damage in buildings with captive columns was observed to decrease with window height-to-column height ratios of more than 20%.